Ethics in educational research: limits and challenges in the face of Artificial Intelligence (Práxis Educativa, 2025)
This article presents reflections on ethics in the field of educational research, examining both regulatory frameworks and the new dimensions the issue assumes with the integration of new digital technologies, primarily Artificial Intelligence (AI). The theoretical and methodological premise is based on critical thinking, emphasizing that ethical issues entail a political dimension rooted in social and historical conditions. The text revisits current debates on AI in educational research and questions the necessity of institutional regulatory frameworks to guide scientific research in the Humanities, particularly in the field of Education.Keywords: Research ethics. Ethics in educational research. AI in educational research.